Strategi Pengembangan Produk Dalam Peningkatan Penjualan Rumah Makan Sudi Mampir Palangka Raya - Alexandro, Rinto; Hariatama , Fendy; Lenlioni, Liling (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
This article discusses the importance of economic growth in improving people's welfare, with a focus on the culinary business sector in Indonesia. In this context, the Sudi Mampir restaurant in Palangka Raya is the object of research to examine product development strategies that contribute to increased sales. The purpose of this study is to obtain data on product development strategies in increasing sales at the Sudi Mampir restaurant in Palangka Raya. This article summarizes the essence of qualitative research methods that involve collecting and analyzing data in the form of text, images, or sounds. This method emphasizes interpretation, theory development, and understanding of social context. The overall analysis shows that product development carried out effectively by Rumah Makan Sudi Mampir Palangka Raya has a positive impact on increasing sales. The results of this study provide deep insight into the importance of understanding customer preferences, price adjustments, and innovation in menu variations to increase competitiveness in the culinary industry